PENGARUH DIGITAL MARKETING UMKM MAKANAN MINUMAN TERHADAP KINERJA PEMASARAN MELALUI INOVASI PRODUK DI KOTA PANGKALPINANG (The Influence Of Digital Marketing For Food And Beverage Msmes On Marketing Performance Through Product Innovation In The City Of Pangkalpinang) - NINGSIH, GIAN; KARSININGSIH, ENI; PURWASIH, RATI (Universitas Mulawarman (University of Mulawarman), 2024)
This research aims to analyze the influence of digital marketing on marketing performance and product innovation, analyze the influence of product innovation on marketing performance, and analyze the influence of digital marketing on marketing performance through product innovation in food and beverage processing msmes in Pangkalpinang City. . The research method used is a survey method. Meanwhile, the sampling method used was purposive sampling (intentionally) with a sample size of 65 respondents. The analysis method uses sem-pls (structural equation modeling-partial least square) analysis with smartpls software version 4.0. The research results show that digital marketing has a direct positive effect on product innovation and product innovation has a positive effect on marketing performance, but digital marketing has no direct effect on marketing performance. Meanwhile, digital marketing indirectly has a positive effect on marketing performance through product innovation.